Dark soliton and periodic wave solutions of nonlinear evolution equations - Guner, Ozkan; Bekir, Ahmet; Cevikel, Adem Cengiz (SPRINGEROPEN, 2013)
This paper studies the Kudryashov-Sinelshchikov and Jimbo-Miwa equations. Subsequently, we formally derive the dark (topological) soliton solutions for these equations. By using the sine-cosine method, some additional periodic solutions are derived. The physical parameters in the soliton solutions of the ansatz method, amplitude, inverse width and velocity, are obtained as functions of the dependent model coefficients.
Keywords: dark soliton; sine-cosine method; ansatz method; Kudryashov-Sinelshchikov equation; Jimbo-Miwa equation; IMPROVED F-EXPANSION; TANH METHOD; (G'/G)-EXPANSION METHOD; N) EQUATION; KDV; BRIGHT; Mathematics